Christianity made in Japan : a study of indigenous movements - Mullins, Mark (University of Hawai'i Press, 1998)
For centuries the accommodation between Japan and Christianity has been an uneasy one. Compared with others of its Asian neighbors, the churches in Japan have never counted more than a small minority of believers more or less resigned to patterns of ritual and belief transplanted from the West. But there is another side to the story, one little known and rarely told: the rise of indigenous movements aimed at a Christianity that is at once made in Japan and faithful to the scriptures and apostolic tradition. Christianity Made in Japan draws on extensive field research to give an intriguing and sympathetic look behind the scenes and into the lives of the leaders and followers of several indigenous movements in Japan. Focusing on the "native" response rather than Western missionary efforts and intentions, it presents varieties of new interpretations of the Christian tradition. It gives voice to the unheard perceptions and views of many Japanese Christians, while raising questions vital to the self-understanding of Christianity as a truly "world religion."This ground-breaking study makes a largely unknown religious world accessible to outsiders for the first time. Students and scholars alike will find it a valuable addition to the literature on Japanese religions and society and on the development of Christianity outside the West. By offering an alternative approach to the study and understanding of Christianity as a world religion and the complicated process of cross-cultural diffusion, it represents a landmark that will define future research in the field
Keywords: Christian sects -- Japan.; Japan -- Church history.; Christianity and culture -- Japan.; Sectes chrétiennes -- Japon.; Christianisme et civilisation -- Japon.; Japon -- Histoire religieuse.; RELIGION -- Christianity -- History.; RELIGION -- Christianity -- General.; Christian sects; Christianity and culture; Japan; Godsdienstige bewegingen.; Christendom.; Christianisme et culture.; Church history